2022
DOI: 10.1136/bmjopen-2021-056868
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic differences in patient experience with primary care during COVID-19: results from a cross-sectional survey in Ontario, Canada

Abstract: PurposeWe sought to understand patients’ care-seeking behaviours early in the pandemic, their use and views of different virtual care modalities, and whether these differed by sociodemographic factors.MethodsWe conducted a multisite cross-sectional patient experience survey at 13 academic primary care teaching practices between May and June 2020. An anonymised link to an electronic survey was sent to a subset of patients with a valid email address on file; sampling was based on birth month. For each question, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…This may also be due to a multitude of social and behavioral factors. First, several surveys in North America suggested that some people with acute illness did not seek medical attention and be admitted to hospitals when required 29–31 . This deficiency in care‐seeking behavior could have been compounded by deficiencies in the outpatient care setting as well, 32–34 as evident by a reduction in inpatient and outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be due to a multitude of social and behavioral factors. First, several surveys in North America suggested that some people with acute illness did not seek medical attention and be admitted to hospitals when required 29–31 . This deficiency in care‐seeking behavior could have been compounded by deficiencies in the outpatient care setting as well, 32–34 as evident by a reduction in inpatient and outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…1,33 In US studies, virtual care often includes a high portion of video unlike in Ontario where most virtual care was delivered by phone. 3…”
Section: Discussionmentioning
confidence: 99%
“…2 Research has found that most patients feel comfortable with virtual care, like its convenience, and want it to continue. 3-6 However, there are concerns about the impact of virtual primary care visits on care quality including on patient safety, 7 equity in access, 8,9 effective chronic condition management, 10 and healthcare utilization. 11 Effects have been hard to untangle due to the simultaneous impact of the pandemic on care.…”
Section: Introductionmentioning
confidence: 99%
“…A higher proportion of those with trouble making ends meet and those with lower self-rated health reported delays in seeking care. 95 Providing Care for Patients Awaiting Disrupted Surgeries and Services…”
Section: Responding To Shifting Priorities Through Changes In Volume ...mentioning
confidence: 99%
“…118,119 Net new virtual care in Ontario was overwhelmingly done by telephone. 95 In the first four months of the pandemic, virtual primary care increased dramatically, comprising 71.1% of primary care physician visits. 92 The proportion of care delivered virtually subsequently decreased and then fluctuated.…”
Section: Providing Preventive Carementioning
confidence: 99%